1952
DOI: 10.1021/ac60061a022
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Organic Compounds

Abstract: HE accepted requirements for full characterization of an T organic compound include establishment of purity of sample, determination, of physical properties, determination of elementary composition, functional groups, and empirical formula, and elucidation of structural formula and spatial relationships. It is evident that identification of a known molecule will involve less extensive investigation than full characterization of a complex new compound. The characterization of simple or complex compounds may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1953
1953
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 231 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…In an update on methods for organic compound characterization in 1952, Peck and Gale pointed out that "The accepted requirements for full characterization of an organic compound include establishment of purity of sample, determination, of physical properties, determination of elementary composition, functional groups, and empirical formula, and elucidation of structural formula and spatial relationships." 1 This thought was written well over half a century ago, but few papers on nanoscale materials today would meet these ideal requirements.…”
Section: Standardizing Nanomaterialsmentioning
confidence: 99%
“…In an update on methods for organic compound characterization in 1952, Peck and Gale pointed out that "The accepted requirements for full characterization of an organic compound include establishment of purity of sample, determination, of physical properties, determination of elementary composition, functional groups, and empirical formula, and elucidation of structural formula and spatial relationships." 1 This thought was written well over half a century ago, but few papers on nanoscale materials today would meet these ideal requirements.…”
Section: Standardizing Nanomaterialsmentioning
confidence: 99%
“…Their advantages in biological inert, optical, and photothermal properties and shape-, size-, and surface chemistry-adjusted performance in vivo , made GNPs the promising material in the future as has been approved by the Food and Drug Administration (FDA). , However, there is no any business or national standards for the medicinal application of GNPs yet. As early as 1952, Peck and Gale suggested that the accepted requirements for full characterization of an organic compound place emphasis on the analysis of sample purity, physical properties, elementary composition, functional groups, and spatial relationships based on structural formula . On the contrary, the criteria of nanomaterials would focus on the analytical methods of main ingredients and limits of impurities as well as their possible influence on the biosafety.…”
Section: Introductionmentioning
confidence: 99%
“…As early as 1952, Peck and Gale suggested that the accepted requirements for full characterization of an organic compound place emphasis on the analysis of sample purity, physical properties, elementary composition, functional groups, and spatial relationships based on structural formula. 19 On the contrary, the criteria of nanomaterials would focus on the analytical methods of main ingredients and limits of impurities as well as their possible influence on the biosafety. Herein, to discuss the quality control of gold-based nanomaterials, we chose the simplest and most widely utilized citratereduced GNPs as a demonstration to establish the analytical methods for main ingredients and impurities.…”
Section: ■ Introductionmentioning
confidence: 99%
“…11 Identification of many organic functional groups is carried out using FT-IR due to the unique oscillation frequencies of the corresponding bonds. 12 The analysis of any FT-IR spectrum takes a lot of time even for qualified scientists. Therefore, the interpretation of FT-IR spectra by using ML methods is a promising and interesting task.…”
Section: Introductionmentioning
confidence: 99%